Responses to stimulate substitution and cascade use of wood within a wood use system: Experience from Bavaria, Germany. (January 2018) - Winder, Gordon M.; Bobar, Amra
Abstract: The ideas of cascade use within the wood use system and innovation of new wood-based materials and applications to substitute for other materials have recently gained new impulse within Germany since they have been declared to be priorities within the German government's climate change related policies. This paper explores responses to government policies for a sustainability transition through more intensive and efficient use of wood among Bavarian enterprises. It is based upon interviews with architects, officials, and enterprise owners and managers conducted in 2015 and 2016. The research identifies the opportunities for and barriers to substitution and cascade use of wood as perceived by managers of enterprises embedded in the wood use system. The paper assesses whether the enterprises studied are ready to be change agents in the envisioned sustainability transition. It also maps out the complex Bavarian institutional context within which innovative uses of wood are taking place.